Analysis of The Influence of Factors on Maritime Cyber Resilience on Board With Intervening Maritime Cyber Security Awareness - Hendriawan, Arizal; Gautama, Idris; Siahaan, Denny; Kurniawan, Kurniawan (Syntax Literate, 2025)
Indonesia plays a crucial role in sustaining the global maritime industry, with its growing potential to supply a skilled workforce through improved maritime education and international certifications. However, cybersecurity has become a critical challenge, with rising cyberattacks causing financial losses, operational disruptions, and diminished trust among stakeholders. Limited digital literacy, outdated technology, and inadequate cyber threat training exacerbate vulnerabilities, threatening maritime operations, national security, and economic stability. This study evaluates maritime cybersecurity management systems and assesses the readiness of Indonesian seafarers in addressing cyber threats. A quantitative approach is employed, using questionnaires distributed to officer-level seafarers holding Certificates of Endorsement (COE). A sample of 396 respondents, determined through the Slovin formula and purposive sampling, was analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results show that Digital Literacy significantly enhances Maritime Cybersecurity Awareness but does not directly impact Cybersecurity Resilience. In contrast, System & Technology Availability has a direct and significant influence on Resilience, particularly through enhanced infrastructure and security measures. Maritime Cybersecurity Awareness also mediates the relationship between Digital Literacy and Resilience, emphasizing its critical role in improving preparedness.The study recommends enhancing digital literacy through targeted training, upgrading technological infrastructure, conducting specialized cybersecurity programs, and enforcing stricter regulatory policies. These steps are crucial to strengthening maritime cybersecurity resilience and fostering a secure, adaptive maritime ecosystem in Indonesia.